2017
DOI: 10.1055/s-0043-108998
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a New Device (WIMU®) for Measuring Hamstring Muscle Extensibility

Abstract: The aims of the current study were 1) to evaluate the validity of the WIMU system for measuring hamstring muscle extensibility in the passive straight leg raise (PSLR) test using an inclinometer for the criterion and 2) to determine the test-retest reliability of the WIMU system to measure hamstring muscle extensibility during the PSLR test. 55 subjects were evaluated on 2 separate occasions. Data from a Unilever inclinometer and WIMU system were collected simultaneously. Intraclass correlation coefficients (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 38 publications
3
19
0
3
Order By: Relevance
“…In addition, the ICC and R 2 for both paces were greater than 0.96 (p < 0.001). A previous analysis of the concurrent validity of WIMU Pro for the analysis of the range of motion during flexion and extension of the hip in a straight leg raise test [29] found similar results (difference = 0.5 • , ICC = 0.99, and R 2 = 0.99), although the SEM was lower (0.05).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In addition, the ICC and R 2 for both paces were greater than 0.96 (p < 0.001). A previous analysis of the concurrent validity of WIMU Pro for the analysis of the range of motion during flexion and extension of the hip in a straight leg raise test [29] found similar results (difference = 0.5 • , ICC = 0.99, and R 2 = 0.99), although the SEM was lower (0.05).…”
Section: Discussionmentioning
confidence: 60%
“…Other researchers who have analyzed the reliability of gold standard technology for analyzing the range of motion of the hip [36] found an ICC of 0.92, CV of 3.6 • , and SEM of 1.9 • . A previous study of the reliability of the WIMU Pro device when used to measure the range of motion in hip flexion-extension [29] reported an ICC of 0.984, CV of 0.01%, and SEM of 0.31 • .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There were no significant differences between instruments for left ankle measurement (p > 0.05) even though a significant systematic bias (~1.77°) with medium effect The data from the inertial device was compared to a Unilever inclinometer (ISOMED, Inc., Portland, OR, USA). The inclinometer was considered as the reference instrument because it is defined as a valid and reliable instrument for assessing ankle dorsiflexion [14,29,30] and several other joints' range of motion (e.g., hip flexion) [31]. The inclinometer was placed on top of the device following similar previous testing procedures [31] and the start point was set at a 90 degree knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this inertial device has been previously validated for clinical purposes (e.g., hamstring extensibility in the passive straight leg raise test [31]). This study showed similar results in systematic bias (<0.5°), SEM (<0.43°), and an ICC very close to 1 (0.99) [31]. However, there are studies that have specifically • : degrees; mean ± standard deviation; CI: confidence interval; SEM: standard error of the measurement; ICC: intraclass correlation coefficient; CV: coefficient of variation; * p ≤ 0.01; † p ≤ 0.001.…”
Section: Discussionmentioning
confidence: 99%